FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KEKAMBUHAN PADA PASIEN HALUSINASI PENDENGARAN DI RUANGAN NYIUR RUMAH SAKIT KHUSUS DAERAH PROVINSI SULAWESI SELATAN - Elmiana Bongga Linggi (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2018)
Recrudescence is a revival or reappearance acute symptoms which is usually same with previous period. There are some factors cause the recrudenscence such as, patient is insubordinate consuming the medicine, controlling by doctor is not organizingly and the lack of motivation by social and family. The aim of this research is to find out some factors related to recrudescence by hearing hallucination in Nyiur room, Regional Private Hospital South Sulawesi. The research design is analytical observational with sampling method is purposive sampling and total sample are 44 respondents. Technic of collecting data are questionnaire, and documentation. Statistic test by using chi-square tes, signific ant value p<? with ?= 0,05 (5%). All of the datum use statistic test to find out correlation between two variable,for the pursuance in consuming the medicine p= 0,001, the motivation of family p=0,024, social motivation p=0,004. Therefore, there is correlation between the pursuance in consuming the medicine, the motivation of family and social recrudescence on hearing hallucination patien in Regional Private Hospital South Sulawesi.